NOVEL MAGNETISM IN PERMANENT MAGNETS - R. Griissinger (Jurnal Sains Materi Indonesia, 2003)
An overview on the physics of hard magnetic materials is given. The basic considerations leading to hard magnetic properties are discussed. All groups of industrial permanent magnets such as: Al-Ni-Co, ferrites. Sm-Co based, Nd-Fe-B are presented. The most important production methods are described. The advantage and disadvantages of each magnet group is given.